A crown of swords eaudiobook - Jordan, Robert (Wheel of Time,, 2007)
The Wheel of Time is now an original series on Prime Video, starring Rosamund Pike as Moiraine! In A Crown of Swords , the seventh novel in Robert Jordan's #1 New York Times bestselling epic fantasy series, The Wheel of Time®, a rebellious uprising threatens Rand al'Thor's rule as he prepares to battle an even more dangerous enemy. Incited by nobles seeking to reclaim their places of power, armies march against the Dragon Reborn. As Rand tries to restore order, he discovers a lack of loyalty even among the warrior Aiel, and still mistrusts the rebel Aes Sedai even though they swore allegiance. But nothing can stop Rand and his Asha'man soldiers from storming the city of Illian to confront the Forsaken Sammael, and challenge him to a duel of the One Power with the winner taking the Crown of Swords... Since its debut in 1990, The Wheel of Time® by Robert Jordan has captivated millions of readers around the globe with its scope, originality, and compelling characters. The last six books in series were all instant #1 New York Times bestsellers, and The Eye of the World was named one of America's best-loved novels by PBS's The Great American Read. The Wheel of Time® New Spring: The Novel #1 The Eye of the World #2 The Great Hunt #3 The Dragon Reborn #4 The Shadow Rising #5 The Fires of Heaven #6 Lord of Chaos #7 A Crown of Swords #8 The Path of Daggers #9 Winter's Heart #10 Crossroads of Twilight #11 Knife of Dreams By Robert Jordan and Brandon Sanderson #12 The Gathering Storm #13 Towers of Midnight #14 A Memory of Light By Robert Jordan and Teresa Patterson The World of Robert Jordan's The Wheel of Time By Robert Jordan, Harriet McDougal, Alan Romanczuk, and Maria Simons The Wheel of Time Companion By Robert Jordan and Amy Romanczuk Patterns of the Wheel: Coloring Art Based on Robert Jordan's The Wheel of Time